Magnetic properties of γ-Fe2O3 nanoparticles in a porous SiO2 shell for drug delivery. (13th November 2020) - Kamali, S; Yu, E; Bates, B; McBride, J R; Johnson, C E; Taufour, V; Stroeve, P
Abstract: A method is presented for synthesizing core–shell nanoparticles with a magnetic core and a porous shell suitable for drug delivery and other medical applications. The core contains multiple γ -Fe2 O3 nanoparticles (∼15 nm) enclosed in a SiO2 (∼100–200 nm) matrix using either methyl (denoted TMOS- γ -Fe2 O3 ) or ethyl (TEOS- γ -Fe2 O3 ) template groups. Low-temperature Mössbauer spectroscopy showed that the magnetic nanoparticles have the maghemite structure, γ -Fe2 O3, with all the vacancies in the octahedral sites. Saturation magnetization measurements revealed that the density of γ -Fe2 O3 was greater in the TMOS- γ -Fe2 O3 nanoparticles than TEOS- γ -Fe2 O3 nanoparticles, presumably because of the smaller methyl group. Magnetization measurements showed that the blocking temperature is around room temperature for the TMOS- γ -Fe2 O3 and around 250 K for the TEOS- γ -Fe2 O3 . Three dimensional topography analysis shows clearly that the magnetic nanoparticles are not only at the surface but have penetrated deep in the silica to form the core–shell structure.